Preparation method of high-toughness silk fibroin hydrogel

Through the processing method of directed freezing and heating stretching of silk fibroin in silk, a silk fibroin hydrogel scaffold with high mechanical properties and good biocompatibility was prepared, which solved the problem of insufficient mechanical properties of existing tendon patch materials, and achieved similar mechanical strength and higher repair efficiency as the rotator cuff tendon in human body.

CN119684635AActive Publication Date: 2025-03-25LIANGZHU LAB +1

Patent Information

Application Number
CN202311241159.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25
Estimated Expiration
2043-09-22

AI Technical Summary

Technical Problem

The existing tendon patch materials have shortcomings in terms of mechanical properties and biocompatibility, making it difficult to achieve a mechanical strength similar to the rotator cuff tendon in the human body, and have poor repair results.

Method used

By performing directed freezing and heating coaxial stretching of silk fibroin in natural silk, a high-toughness silk fibroin hydrogel scaffold with a micro-directed channel structure is formed.

Benefits of technology

It significantly improves the maximum tensile strength of the silk hydrogel, achieves a mechanical strength similar to the rotator cuff tendon in the human body, and has good biocompatibility and degradability, promoting efficient repair of the tendon.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684635A_ABST
    Figure CN119684635A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of silk fibroin hydrogel with high strength and high biocompatibility, a natural silk fibroin material is utilized, a processing method of directional freezing and heating coaxial stretching is adopted, and the heating temperature needs to be higher than the glass transition temperature of the silk fibroin material, so that the maximum tensile strength of a silk fibroin hydrogel bracket is improved; and a micro directional pore channel structure is formed, so that the mechanically enhanced hydrogel stent with good biocompatibility is finally obtained. A rotator cuff patch prepared by adopting the hydrogel scaffold can achieve the mechanical strength similar to that of rotator cuff tendons in a human body, and has good biocompatibility, and the microstructure has micron-scale directional pore channels, so that directional growth of cells on the surface and in the material is facilitated, and higher repair efficiency can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogel preparation, and in particular to a method for preparing a high-toughness silk fibroin hydrogel, and in particular to a method for preparing a high-toughness silk fibroin hydrogel that can be used as a rotator cuff patch, anterior cruciate ligament substitute, etc. Background Art

[0002] Tendon injury is one of the common sports injuries. Natural tendons are mainly composed of dense type I collagen, with low cell content and weak angiogenesis ability, so it is difficult to heal after injury. Patients with large-scale tendon injuries such as giant rotator cuff tears and anterior cruciate ligament tears often need to use patches for auxiliary treatment. There are many methods for preparing tendon patches. Traditional technologies such as autologous materials and allogeneic material patches have problems such as insufficient sources and easy to cause donor site complications; existing artificial patches have disadvantages such as low mechanical strength of synthetic material scaffolds and strong immunogenicity. These shortcomings lead to poor tendon repair effects, and finding a patch material with excellent mechanical properties and biocompatibility has become a research hotspot.

[0003] Silk fibroin is widely used in the preparation of tissue engineering scaffolds. It has good biocompatibility, degradability, and excellent mechanical properties. Silk fibroin is abundant in sources and can be extracted from silk. Silk has a unique protein polymer structure, with silk fibroin as the core and sericin attached to the surface. Silk fibroin can be obtained by degumming silk. Silk fibroin contains 18 kinds of amino acids, most of which are glycine, alanine and serine. Silk fibroin can be completely degraded in the body. During its degradation process, the cell microenvironment will be enriched with a large number of amino acids, especially proline and lysine, which are the main raw materials for collagen synthesis. The repeated GAGAG sequence in silk fibroin can form a secondary structure β-fold through self-assembly, which gives silk fibroin excellent mechanical strength and toughness. It is reported that the toughness of silk fibroin can even be better than the best synthetic materials. At the same time, silk fibroin has adjustable mechanical properties. By adjusting the proportion of β-fold structure in silk fibroin, the mechanical strength of silk material can be further improved, and it is better than most of the currently commonly used degradable polymer materials, such as collagen, polylactic acid, etc. In addition, the surface of silk materials is easy to process and modify, and can be processed into various forms from liquid solutions to organic solids, such as gels, tubes, hydrogels, microspheres, films, etc. These characteristics of silk materials give them broad prospects in tissue engineering applications. However, the mechanical strength of existing silk fibroin is still difficult to reach the mechanical strength similar to that of the rotator cuff tendon in the human body, so there is an urgent need to find a silk fibroin with better mechanical properties. Summary of the invention

[0004] To solve the above problems, the present invention provides a method for preparing a high-toughness silk fibroin hydrogel that can be used as a tendon patch. The method utilizes natural silk material and a processing method of directional freezing and heating coaxial stretching (higher than the glass transition temperature of the silk material) to achieve an improvement in the maximum tensile strength of the silk hydrogel scaffold, and has a microscopic directional pore structure. Finally, a mechanically enhanced hydrogel material with good biocompatibility is obtained, which can be used to prepare tendon patches and can achieve a mechanical strength similar to that of the rotator cuff tendon in the human body, and has good biocompatibility and degradability. The microscopic morphology has micrometer-scale directional pores, which are conducive to the directional growth of cells on the surface and inside of the material, and can achieve higher repair efficiency.

[0005] On the one hand, the present invention provides a method for preparing a hydrogel, which is mainly prepared by directional freezing and freeze-drying a silk fibroin solution, and then heating and stretching it.

[0006] The silk fibroin solution of the invention is prepared by degumming natural silk.

[0007] Directional freezing technology is to place a polymer solution in a temperature field to cool it down. As the temperature decreases, the solvent (usually water) gradually solidifies along the temperature gradient, and the ice crystal columns produced by solidification squeeze, rearrange, and embed the polymer chains between the ice crystal columns. In this process, ice crystals act as an orientation template for polymer chains and play a role of physical confinement. Directional freezing can form anisotropic structures, allowing materials to be arranged in different orientations in space, and the mechanical properties in the orientation direction will be much stronger than before directed freezing; in addition, due to the space-occupying effect of ice crystals, the local aggregation of silk molecules will increase, further enhancing the mechanical properties. Compared with ordinary silk hydrogels that are not directional frozen, the maximum tensile stress of directional frozen silk hydrogels can be enhanced several times. In addition, through directional freezing technology, silk solutions can form parallel arranged pipeline structures with parallel pores of 5-10um, similar to the microstructure of tendons. This microstructure, on the one hand, can guide and stimulate tendon stem cells to differentiate into tendon cells, and on the other hand, it is beneficial for cells to penetrate, grow and arrange themselves in a directional manner inside the scaffold, thereby promoting the efficiency and effectiveness of tendon regeneration.

[0008] Then, the present invention heats and coaxially stretches the silk material, wherein the heating temperature is higher than the glass transition temperature of the silk material. The mechanical properties of the material can be greatly improved by heating and coaxially stretching.

[0009] Coaxial stretching is to give a certain strain to the material and stretch it to a certain length. The molecules in the material will rearrange under the action of the tensile stress generated, so that the material has a certain orientation structure in the stretching direction and enhances the tensile strength in this orientation. In addition, amorphous polymers have three mechanical states, namely glass state, high elastic state and viscous flow state. When the temperature is low, the material is a rigid solid, similar to glass, and only very small deformation will occur under the action of external force. This state is the glass state; when the temperature continues to rise to a certain range, the deformation of the material increases significantly, and the deformation is relatively stable in a certain temperature range thereafter. This state is the high elastic state. The glass transition temperature (Tg) refers to the temperature corresponding to the transition from the glass state to the high elastic state. Silk is in a glassy state at room temperature and can only undergo small deformation during coaxial stretching. When heated above Tg, silk enters a highly elastic state, the movement of silk molecules intensifies, and the range of activity increases. Silk materials in this state are more susceptible to deformation and can be stretched to a higher ratio during coaxial stretching. In addition, the intensified molecular movement is more conducive to the formation of molecular-level orientation.

[0010] The glass transition temperature of the dried silk film is about 178°C. When water molecules are used as plasticizers, the conditions adopted in the present invention can reduce the glass transition temperature to 77°C, which greatly simplifies the operation difficulty and reduces the cost.

[0011] The present invention can increase the maximum tensile stress of the silk hydrogel by about 10 times by coaxially stretching the hydrated silk at different temperatures above Tg and with different tensile strains.

[0012] The directional freezing and heating stretching adopted in the present invention also have a significant synergistic effect, which increases the maximum tensile strength of the silk fibroin hydrogel by nearly 100 times. At the same time, it also has better biocompatibility. The directional pore structure at the microscopic level is conducive to cell growth and is more conducive to the repair of tendon injuries.

[0013] Heating stretching must be performed after directional freezing, and coaxial stretching must be performed along the direction of directional freezing: 1. The directional freezing step is a prerequisite for heating stretching. Direct stretching without directional freezing will cause the silk fibroin hydrogel to break directly; 2. If coaxial stretching is not performed in the direction of directional freezing after directional freezing, it will also cause the silk fibroin hydrogel to break directly.

[0014] Furthermore, the preparation method comprises the following steps:

[0015] (1) pouring the silk fibroin solution into a mold and performing directional freezing to obtain silk fibroin ice cubes;

[0016] (2) freeze-drying and cross-linking the silk fibroin ice cubes, and then soaking them in water for hydration to obtain a hydrogel;

[0017] (3) Heating and stretching the hydrogel.

[0018] Furthermore, the directional freezing described in step (1) refers to placing a freezing source close to a mold so that the silk solution in the mold forms ice crystals starting from a contact surface close to the freezing source and moving away from the contact surface of the freezing source, wherein the temperature of the freezing source is lower than -20°C.

[0019] Any device or product that has the effect of lowering temperature can be used as a refrigeration source in the present invention.

[0020] Furthermore, step (1) is: pouring the silk fibroin solution into the columnar space in the mold; placing the mold above the metal rod, and immersing one side of the metal rod in liquid nitrogen.

[0021] In some methods, a metal rod serving as a freezing source is located below the mold and is in complete contact with the bottom surface of the mold. During freezing, ice crystals of the silk material grow upward from the cold source below, thus having a certain directionality, which is perpendicular to the bottom surface contacted by the freezing source, and then grows in a direction away from the freezing source.

[0022] In some methods, a metal rod serving as a freezing source is located on the side of the mold and is in complete contact with the side of the mold. During freezing, ice crystals of the silk material begin to grow directionally from the side in contact with the freezing source. The direction in which the ice crystals grow is perpendicular to the bottom surface of the freezing source, and then grow in a direction away from the freezing source.

[0023] In some methods, a metal rod serving as a freezing source is located on the top surface of the mold and is in complete contact with the top surface of the mold. During freezing, ice crystals of the silk material begin to grow downward from the top surface in contact with the freezing source. The direction in which the ice crystals grow is perpendicular to the bottom surface of the freezing source, and then grow in a direction away from the freezing source.

[0024] In some embodiments, step (1) is as follows: pour the silk fibroin solution into a mold, wherein there is a columnar space of 4*4*20 mm in the mold. The mold is placed on top of an aluminum rod, the width of which can completely cover the contact surface with the mold, and one side of the aluminum rod is immersed in liquid nitrogen. After 10 minutes, the mold is removed, the silk fibroin ice cube inside is taken out, and placed in a -80°C refrigerator overnight.

[0025] Furthermore, the cross-linking in step (2) is chemical cross-linking or enzyme cross-linking.

[0026] Since silk fibroin is soluble in water, it needs to be cross-linked to form a hydrogel. Cross-linking can keep the silk fibroin scaffold stable in the aqueous solution and further improve the strength of the material.

[0027] It should be noted that the cross-linking treatment must be performed after the directional freezing is completed. Because if the cross-linking is performed first, the molecular structure will be fixed in advance, and it will no longer be able to be arranged in a directional manner as the ice crystals grow during directional freezing, and directional micro-pores cannot be formed, so that the scaffold will eventually lose its directional structure.

[0028] The present invention can adopt any method for crosslinking, such as ethanol crosslinking, other chemical methods crosslinking, enzyme crosslinking, etc. As long as the crosslinking of silk material can be achieved, it can be used in the present invention and is within the protection scope of the present invention.

[0029] Furthermore, step (2) is: placing the silk fibroin ice cube in a freeze dryer for freeze drying, then immersing it in anhydrous ethanol for cross-linking, and then immersing it in water for full hydration.

[0030] In some embodiments, the present invention uses anhydrous ethanol for cross-linking. Before cross-linking, the silk fibroin ice cubes need to be freeze-dried first. This is because if the silk fibroin ice cubes are directly cross-linked without freeze-drying, the low-temperature silk fibroin ice cubes will encounter relatively high-temperature ethanol, and the internal microstructure will be destroyed as the ice crystals melt before the ethanol cross-linking. After the silk fibroin ice cubes are freeze-dried, a complete silk fibroin scaffold with a microscopic oriented structure is obtained, and then anhydrous ethanol is placed for intermolecular cross-linking to form a more stable silk fibroin hydrogel structure.

[0031] After cross-linking, the hydrogel needs to be immersed in water for hydration. This is because: the glass transition temperature of dry silk material is about 178°C, and with the change of humidity, when water molecules are used as plasticizers, the glass transition temperature can be reduced to below 77°C. After lowering the glass transition temperature, the difficulty of heating and stretching operations is greatly simplified, and the cost is reduced. In addition, when coaxial stretching is performed at a temperature above 100 degrees, the water in the hydrogel will evaporate quickly, resulting in the loss of water molecules as plasticizers, making the hydrogel brittle and limiting the stretching length.

[0032] Sufficient hydration means that the weight of the stent remains basically unchanged after being soaked in water, indicating that the hydration is sufficient. Generally, it is soaked for more than 48 hours.

[0033] In some methods, the silk fibroin ice cubes can be placed in a freeze dryer for freeze drying for 72 hours to obtain a dry scaffold, which is then immersed in anhydrous ethanol for cross-linking for 6 hours, and then immersed in water for 48 hours to ensure full hydration.

[0034] Furthermore, the heating stretching in step (3) refers to heating to a temperature above the glass transition temperature of the silk fibroin and then coaxial stretching, wherein the direction of the coaxial stretching is consistent with the direction of directional freezing.

[0035] The direction of coaxial stretching is consistent with the direction of directional freezing, which makes the mechanical properties of the prepared scaffold better, and the presence of directional micro-pores is conducive to the growth of cells.

[0036] After directional freezing, drying and cross-linking, the hydrogel has vertical stripes on the surface, and the direction of the microscopic pores formed by directional freezing can be distinguished by the naked eye. At this time, it is heated to above the glass transition temperature of silk protein, and then directional coaxially stretched in the same direction to achieve a rapid increase in mechanical strength.

[0037] Furthermore, step (3) is: the hydrated hydrogel is first preheated at a temperature of 25-130° C., and then the material is stretched by 30-90% of the initial length.

[0038] In some embodiments, the heating temperature only needs to be above the glass transition temperature of the silk fibroin, and the glass transition temperature of the hydrated silk fibroin hydrogel can be reduced to below 77°C, such as 25°C.

[0039] Furthermore, step (3) is as follows: the hydrated hydrogel is preheated at a temperature of 25-130° C. for 5 minutes, and then the material is stretched by 30-90% of the initial length and maintained for 15 minutes. After the stretching, the material is taken out and immersed in water for hydration to obtain the final hydrogel.

[0040] In some methods, the heating and stretching can be performed in a heating and stretching device, such as a high-temperature mechanical testing machine, as long as heating and stretching can be achieved simultaneously.

[0041] In some embodiments, the pre-tensioning force for heat stretching only needs to be able to pull the hydrogel so that the hydrogel does not shrink significantly under the pre-tensioning force.

[0042] In some methods, the ratio of heating and stretching is not fixed. As long as it is stretched, the mechanical properties of the hydrogel can be improved. Therefore, the stretching can be carried out according to the actual needs and the scaffold can be ensured not to be broken. When the material is stretched to more than 90% of the initial length, it may be partially broken.

[0043] In some embodiments, step (3) is: giving the hydrated hydrogel a pre-tension of 2N, preheating at 95°C for 5 minutes, then stretching the material by 30-90% of the initial length at a rate of 10 mm / min at 95°C, and maintaining for 15 minutes. After completion, taking it out and soaking it in water for hydration to obtain the final hydrogel.

[0044] Furthermore, the preparation method of the silk fibroin solution described in step (1) is as follows: after removing the pupae from the silkworm cocoons, the silk is degummed by boiling with 0.02M sodium carbonate for 30 minutes, and the degummed silk fibroin fibers are dried in a fume hood for 12 hours; dissolved in 9.3M lithium bromide at 60°C for 4 hours; the solution is dialyzed for 72 hours using a dialysis bag to remove the lithium bromide; the obtained solution is naturally air-dried in a fume hood for 6 hours to obtain a silk fibroin solution with a concentration of 15%.

[0045] The present invention utilizes natural silk, degumming the silk to prepare a silk fibroin solution, directionally freezing and freeze-drying the silk fibroin solution, and then cross-linking it with anhydrous ethanol. After the obtained scaffold is fully hydrated, it is stretched to 60% of the initial length at a rate of 10 mm / min under high temperature conditions higher than the glass transition temperature (95°C). After maintaining for 15 minutes, the scaffold is taken out and hydrated again to obtain the final hydrogel.

[0046] On the other hand, the present invention provides a method for improving the mechanical properties of materials, wherein the method comprises first directionally freezing and freeze-drying the material, and then coaxially heating and stretching the material, wherein the heating temperature is higher than the glass transition temperature of the material; the material is PVA, gelatin, etc.

[0047] The present invention provides a collaborative processing method of heating stretching and directional freezing. Among them, directional freezing can not only give the material a microscopic directional pore structure, but also improve the mechanical properties of the material through the formation of the anisotropic structure. Further heating and stretching of the directional frozen material above the glass transition temperature can further significantly improve the mechanical properties of the material and increase the maximum tensile stress of the material. At the same time, the micrometer-scale directional pore structure of the hydrogel can, on the one hand, guide and stimulate the differentiation of cells through the microscopic topological morphology, and on the other hand, facilitate the penetration of cells on the scaffold and accelerate the repair of tissues.

[0048] The coordinated processing method of directional freezing and heating stretching provided by the present invention is not only applicable to silk fibroin materials, but also applicable to improving the mechanical properties of other materials.

[0049] On the other hand, the present invention provides a use of a silk fibroin hydrogel for preparing a rotator cuff patch or anterior cruciate ligament substitute, wherein the silk fibroin hydrogel is obtained by directional freezing and freeze-drying a silk fibroin solution, and then heating and stretching the solution, wherein the heating temperature is higher than the glass transition temperature of the silk fibroin.

[0050] In summary, the processing method of pre-protecting and stretching above the glass transition temperature (referred to as heated stretching) and the processing method of coordinated heated stretching and directional freezing of the present invention are used to improve the mechanical properties of materials and obtain surface micromorphology, which is beneficial to tendon repair efficiency.

[0051] The silk fibroin hydrogel scaffold provided by the present invention has the following beneficial effects:

[0052] 1. Excellent mechanical properties. The maximum stress of traditional silk hydrogel is about 0.02-0.2MPa, while the present invention can reach more than 10MPa, which is hundreds of times higher.

[0053] 2. The directional topological structure of the hydrogel surface can promote the directional arrangement of tendon stem cells;

[0054] 3. Good biocompatibility. The silk material itself has good biocompatibility, and no difficult-to-remove organic reagents are used in the preparation process of the hydrogel scaffold, so that the final scaffold has good biocompatibility;

[0055] 4. Compared with autologous tendons, silk materials have a wide range of sources and a simple preparation process;

[0056] 5. The collaborative processing method of directional freezing and heating stretching provided is not only applicable to silk materials, but also to improving the mechanical properties of other materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 The figure is a flow chart of the preparation of silk fibroin hydrogel scaffold;

[0058] Figure 2 This is a schematic diagram of a mold filled with silk fibroin solution in Example 1 being placed on an aluminum rod for directional freezing, with one end of the aluminum rod being immersed in liquid nitrogen;

[0059] Figure 3 These are SEM images of the hydrogel scaffolds without directional freezing, directional freezing, and directional freezing followed by heating and stretching in Example 2;

[0060] Figure 4 The tensile curves and mechanical comparison diagrams of the samples without directional freezing and after directional freezing in Example 2;

[0061] Figure 5 The mechanical universal testing machine was used to test ND in Example 3. 15 The stress-strain curves of the hydrogels were obtained by tensile tests;

[0062] Figure 6 The mechanical universal testing machine was used to test ND in Example 3. 15 Stress-strain curves obtained from fracture toughness tests of hydrogels;

[0063] Figure 7 The notched ND in Example 3 15 Photographs of the hydrogel during stretching;

[0064] Figure 8 The tensile curves and mechanical comparison diagrams of silk fibroin hydrogels with different concentrations in Example 4;

[0065] Fig. 9 is the DSC graph of the silk fibroin hydrogel prepared in step c in Example 5;

[0066] Fig.10The tensile curve and mechanical comparison diagram of the silk hydrogel obtained by changing the heating temperature in step d in Example 5;

[0067] Fig.11 The tensile curve and mechanical comparison diagram of the silk hydrogel obtained by changing the stretching ratio in step d in Example 6;

[0068] Fig.12 The tensile stress-strain curves of the three groups of hydrogels in Example 7 (left figure), and the maximum tensile stress and Young's modulus obtained (right figure);

[0069] Fig.13 This is the HE staining image of the silk fibroin hydrogel used as the lateral splint for repairing the Achilles tendon rupture in rabbits in Example 8. DETAILED DESCRIPTION

[0070] The preferred embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings. It should be noted that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on it. The raw materials and equipment used in the specific embodiments of the present invention are all known products and are obtained by purchasing commercially available products.

[0071] Example 1 Preparation of the silk fibroin hydrogel scaffold provided by the present invention

[0072] The preparation method of the silk fibroin hydrogel scaffold provided in this embodiment is as follows Figure 1 The process is prepared, comprising the following steps:

[0073] a. Preparation method of silk fibroin solution: Bombyx mori cocoons were boiled with 0.02M sodium carbonate for 30 min; the degummed silk fibroin fibers were dried in a fume hood for 12 h; the fibers were dissolved in 9.3M lithium bromide at 60°C for 4 h; the solution was dialyzed with a dialysis bag for 72 h to remove the lithium bromide; the obtained solution was naturally air-dried in a fume hood for 6 h to obtain a silk fibroin solution with a concentration of 15%.

[0074] b. Directional freezing: Pour the silk solution into a homemade mold with a 4*4*20mm columnar space. Place the mold on top of an aluminum rod, the width of which can completely cover the contact surface with the mold, which is 4*4mm. One side of the aluminum rod is immersed in liquid nitrogen (such as Figure 2 ). After 10 minutes, the mold was removed, the silk fibroin ice cube inside was taken out, and placed in a -80℃ refrigerator overnight.

[0075] c. Ethanol cross-linking: Place the silk fibroin ice cubes in a freeze dryer for 72 hours to obtain a dry scaffold, then immerse it in anhydrous ethanol for cross-linking for 6 hours, and then soak it in water for 24 hours to ensure full hydration.

[0076] d. Heated coaxial stretching: Using a high-temperature mechanical testing machine (Model TSE, WANCE), the hydrated hydrogel was clamped between clamps and given a pre-tension of 2N. The hydrogel was preheated at 95°C for 5 min, and then the material was stretched by 60% of the initial length at a rate of 10 mm / min at 95°C and maintained for 15 min. After the end, the material was taken out and soaked in water for 24 h to obtain the final hydrogel.

[0077] Example 2 Effect of directional freezing on silk fibroin hydrogel

[0078] In this example, two groups of silk fibroin solutions were taken. One group was subjected to directional freezing according to the method provided in Example 1, and then cross-linked with ethanol to prepare directional silk fibroin hydrogel scaffolds (DF); the second group was not subjected to directional freezing. The solution prepared in step a was poured into a mold and directly placed in a -80°C refrigerator. It was then freeze-dried and cross-linked with ethanol to form non-directional silk fibroin hydrogels (ND). The SEM images of the two groups of hydrogel scaffolds prepared are shown in Figure 1. Figure 3 As shown, Figure 3 b is a parallel-arranged tube structure formed after directional freezing, with parallel pores of 1-10um, similar to the surface topology of tendon. Figure 3 a is the SEM image of the non-oriented hydrogel scaffold, and Figure 3 The directional arrangement of the channel structure in b is significantly different. The tensile curves of the two groups of silk fibroin hydrogels are shown in Figure 2. Figure 4 As shown, the left figure is the relationship between the stretching ratio and the tensile stress, and the right figure is the comparison between Young's modulus and tensile stress. 15 , refers to DF prepared with 15% concentration of silk fibroin, ND 15 Refers to NDs prepared with 15% silk fibroin concentration. Figure 4 It can be clearly seen that the tensile stress and Young's modulus of silk fibroin prepared by directional freezing are significantly improved.

[0079] Example 3: Oriented freezing step is a prerequisite for heating and stretching

[0080] This embodiment only involves a silk fibroin hydrogel, the preparation process of which is to pour the solution prepared in step a into a mold, directly put it into a -80°C refrigerator (non-oriented), then freeze-dry and cross-link with ethanol to form a non-oriented silk fibroin hydrogel (ND 15 ND 15 The mechanical properties of the hydrogels were tested by tensile tests. Figure 5 The stress-strain curve is shown in Figure 2. Figure 5 As shown, ND 15The mechanical properties of the ND hydrogel are poor, with a maximum stress of only 0.21 MPa and a fracture strain of about 32%, showing low strength and poor toughness. In order to further test the fracture toughness of the material, a pure shear test experiment was conducted on the ND hydrogel. In this test, a pair of ND hydrogels was tested each time, including an original complete hydrogel (Initial ND) and a pre-notched hydrogel (Notched ND). Each pair of hydrogels was subjected to a tensile test to obtain the following results: Figure 6 The stress-strain curve shown is used to calculate the fracture toughness. Figure 7 Shown is the ND with notch 15 Photographs of the hydrogel during stretching, such as Figure 7 As shown, ND 15 The gap expands rapidly during the stretching process and causes the rapid rupture of the hydrogel under small strain (less than 20%). Figure 6 The calculated fracture toughness, ND 15 The hydrogel exhibited poor fracture toughness. 15 Hydrogels have weak mechanical strength and poor toughness, and will break at small strains, making them unsuitable for subsequent heating and stretching tests. In other words, the directional freezing step is a prerequisite for heating and stretching.

[0081] In addition, for DF prepared by directional freezing 15 If the DF prepared by directional freezing is not oriented in the direction of directional freezing, excellent mechanical properties cannot be obtained, it is difficult to stretch and easy to tear. 15 The directional arrangement of the pipe structure determines that the pipes are easy to separate from each other. If the heating and stretching are not performed in the direction of directional freezing during stretching, DF 15 It is easy to tear and cannot smoothly complete the preparation process of directional freezing combined with heating and stretching.

[0082] Example 4 Effect of silk fibroin concentration on silk fibroin hydrogel

[0083] In this example, four groups of silk fibroin solutions were taken, with concentrations of 5%, 10%, 15%, and 20%, respectively. Each group was subjected to directional freezing according to the method provided in Example 1, and then coaxially stretched by 60% at 95°C to prepare a silk fibroin hydrogel scaffold. The tensile properties of the two groups of hydrogel scaffolds prepared were investigated, and the tensile properties were tested by a biomechanical testing machine. The tensile curves of silk fibroin hydrogels with different concentrations were obtained as shown in the following figure: Figure 8 As shown, the left figure is the relationship between the stretching ratio and the tensile stress, and the right figure is the comparison between Young's modulus and tensile stress. 15 H 95 S 60It refers to a hydrogel prepared by heating and stretching a 15% concentration of silk fibroin hydrogel at 95°C with a stretching ratio of 60%. Figure 8 It can be seen that with the increase of silk concentration, the orientation effect of the scaffold becomes more and more obvious, and the tensile performance of the scaffold becomes better and better. Theoretically, the tensile performance of silk with a concentration of 20% or above will be further enhanced, but due to the limited freeze-drying effect, the tensile performance will decrease instead. Therefore, we determined 15% as a good silk concentration.

[0084] Example 5 Effects of different heating and stretching temperatures on the properties of silk fibroin hydrogel scaffolds

[0085] In this example, the method provided in Example 1 was used to prepare the silk fibroin hydrogel. First, DSC detection was performed after step c. The results were as follows: Fig. 9 As shown in the figure, in the first heating, with water molecules as plasticizers, the glass transition temperature of silk fibroin is about 77°C, while in the second heating, due to the complete dehydration of the scaffold, the plasticizing effect of water molecules is lost, and the glass transition temperature of the silk scaffold increases to 178°C. Therefore, we set four temperatures in step d, and used different heating temperatures (25°C, 60°C, 95°C, 130°C) for stretching, and investigated the maximum tensile stress of the prepared hydrogel scaffold. The scaffold mechanics was tested using a biomechanical testing machine. The tensile curve and mechanical comparison of the silk fibroin hydrogel Fig.10 As shown in the figure, before the glass transition temperature (77°C), there is no significant difference in the tensile properties of the hydrogel scaffolds prepared at 25°C and 60°C, but after the temperature rises to the glass transition temperature (77°C), the mechanics of the hydrogel scaffolds prepared at 95°C is significantly higher than that of other groups. When the temperature is as high as 130°C, due to the rapid loss of water molecules, the scaffold breaks when stretched to 60%, and the mechanical properties decrease instead. This result proves that heating coaxial stretching at a temperature above the glass transition temperature can significantly enhance the mechanics, and after the water molecules are lost, the glass transition temperature rises and the effect decreases significantly. Therefore, we determined 95°C as a better heating temperature.

[0086] Example 6 Effects of different stretching ratios during heating and stretching on the properties of silk fibroin hydrogel scaffolds

[0087] In this example, the method provided in Example 1 was used to prepare the silk fibroin hydrogel. In step d, four stretching ratios were set. Different stretching ratios (0%, 30%, 60%, and 90%) were used for stretching. The maximum tensile stress of the prepared hydrogel scaffold was investigated. The scaffold mechanics was tested with a biomechanical testing machine. The tensile curve and mechanical comparison of the silk fibroin hydrogel were Fig.11As shown in the figure, as the stretching ratio increases from 0% to 60%, the mechanical properties of the scaffold gradually increase, indicating that the orientation effect of silk increases with the increase of the stretching ratio; when the stretching ratio further increases to 90%, the mechanical properties of the scaffold decrease instead, because the excessively high stretching ratio causes partial breakage of the scaffold. Therefore, we determined that 60% is a good stretching ratio.

[0088] Example 7 Directional freezing and heating stretching have a synergistic effect on improving the mechanical properties of materials

[0089] This embodiment relates to three groups of silk fibroin hydrogels, which are prepared by the three preparation methods mentioned in Example 1, Example 2, and Example 4, respectively, including ND 15 , DF 15 and DF 15 H 95 S 60 Hydrogel. Fig.12 The tensile stress-strain curves of the three groups of hydrogels are shown, as well as the statistically obtained maximum tensile stress and Young's modulus. 15 and DF 15 It can be concluded that without the heating and stretching step, directional freezing alone can increase the maximum stress and Young's modulus of silk fibroin hydrogel by about 6 times and 1 times, respectively. 15 The hydrogel was subjected to heating and stretching treatment, such as Fig.12 As shown, DF 15 H 95 S 60 The maximum stress and Young's modulus of DF were compared with those of DF with simple directional freezing. 15 The hydrogel increased by 6 times and 5 times, which was 47 times and 15 times higher than the ND group.

[0090] In addition, if neither directional freezing nor non-directional freezing is performed and heating stretching is performed directly, it is also difficult to stretch and is very easy to tear.

[0091] Therefore, directional freezing and heating stretching have a synergistic effect on improving the mechanical properties of non-directional hydrogels.

[0092] Example 8 Repair effect of silk fibroin hydrogel obtained under optimal conditions on rabbit tendon rupture model

[0093] DF 15 H 95 S 60 The hydrogel has a tensile strength and Young's modulus similar to that of tendon, and due to the DF 15 H 95 S 60 The hydrogel degrades slowly in vivo and can provide stable mechanical properties for a long time, making it a promising candidate for artificial tendon replacement.15 H 95 S 60 To investigate the potential of hydrogel as a tendon patch, we transected the rabbit Achilles tendon and placed the DF on the tendon while maintaining the tendon tension. 15 H 95 S 60 The hydrogel is sutured to the tendon stump as a lateral splint, providing mechanical compensation and growth template. Fig.13 In the early stage of repair (4 weeks), new tendons appeared in all groups (blue arrows), but the new tendons in the severance group were disordered, with more and rounder nuclei, more angiogenesis, and partial fat formation (yellow arrows); while in the DF group, 15 H 95 S 60 The new tendons of the DF group were basically arranged in parallel. 15 H 95 S 60 The direction of the cell is the same, and the nucleus is basically spindle-shaped, which is more similar to normal tendon. In addition, DF 15 H 95 S 60 There is only a thin layer of fibrosis and immune reaction around it, which shows that DF 15 H 95 S 60 Good biocompatibility. 15 H 95 S 60 There was almost no degradation and high integrity (white arrow). Due to the lack of sufficient mechanical conditions, the ND group broke / displaced, and therefore could not provide effective mechanical support. The new tendons were similar to those in the severance group. At 12 weeks, the new tendons in the ND and severance groups showed a large wave shape, while the DF 15 H 95 S 60 The new tendons in the DF group became more neat. 15 H 95 S 60 The newly formed tendons in the 3 groups were very close to normal tendons and had no obvious pathological differences from normal tendons.

[0094] Although the present invention is disclosed as above, the present invention is not limited thereto. For example, it can be expanded according to its application range in medicine. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A method for preparing a hydrogel, characterized in that: It is made by directional freezing and freeze-drying the silk solution, and then coaxially heating and stretching it.

2. The preparation method according to claim 1, characterized in that The following steps are involved: (1) pouring the silk fibroin solution into a mold and performing directional freezing to obtain silk fibroin ice cubes; (2) freeze-drying and cross-linking the silk fibroin ice cubes, and then soaking them in water for hydration to obtain a hydrogel; (3) Coaxial heating and stretching of hydrogel.

3. The preparation method according to claim 2, characterized in that: The directional freezing described in step (1) refers to placing a freezing source close to a mold so that the silk solution in the mold forms ice crystals starting from a contact surface close to the freezing source and moving away from the contact surface of the freezing source. The temperature of the freezing source is below -20°C.

4. The preparation method according to claim 3, characterized in that: Step (1) is: pouring a silk fibroin solution into the columnar space in the mold; placing the mold above a metal rod, and immersing one side of the metal rod in liquid nitrogen.

5. The preparation method according to claim 4, characterized in that: The cross-linking in step (2) is chemical cross-linking or enzyme cross-linking.

6. The preparation method according to claim 5, characterized in that: Step (2) is: placing the silk fibroin ice cube in a freeze dryer for freeze drying, then soaking it in anhydrous ethanol for cross-linking, and then soaking it in water for full hydration.

7. The preparation method according to any one of claims 2 to 6, characterized in that: The coaxial heating stretching described in step (3) refers to heating to above the glass transition temperature of the silk fibroin and then coaxial stretching, wherein the direction of the coaxial stretching is consistent with the direction of directional freezing.

8. The preparation method according to claim 7, characterized in that: Step (3) is: the hydrated hydrogel is first preheated at a temperature of 25-130° C., and then the material is stretched to 30-90% of the initial length.

9. A method for improving the mechanical properties of a material, characterized in that: The method comprises firstly performing directional freezing and freeze drying on the material, and then performing coaxial heating and stretching, wherein the heating temperature is higher than the glass transition temperature of the material; the material is a protein-based material.

10. A use of silk fibroin hydrogel for preparing rotator cuff patches and anterior cruciate ligament substitutes, characterized in that: The silk fibroin hydrogel is prepared by directional freezing and freeze-drying a silk fibroin solution and then coaxially stretching the solution by heating. The heating temperature needs to be higher than the glass transition temperature of the silk fibroin.

Citation Information

Patent Citations

  • Preparation method of high-strength fibroin hydrogel with parallel structure

    CN116333343A

  • Method for preparing hydrogel and support for culturing cell

    JP2002186847A

Cited By

  • Method for preparing a high-toughness silk fibroin hydrogel as artificial tendon / ligament

    EP4527420A1